High failure rates in treatment of streptococcal periprosthetic joint infection: results from a seven-year retrospective cohort study. (May 2017) - Akgün, D.; Trampuz, A.; Perka, C.; Renz, N.
Abstract : Aims: To investigate the outcomes of treatment of streptococcal periprosthetic joint infection (PJI) involving total knee and hip arthroplasties. Patients and Methods: Streptococcal PJI episodes which occurred between January 2009 and December 2015 were identified from clinical databases. Presentation and clinical outcomes for 30 streptococcal PJIs in 30 patients (12 hip and 18 knee arthroplasties) following treatment were evaluated from the medical notes and at review. The Kaplan-Meier survival method was used to estimate the probability of infection-free survival. The influence of the biofilm active antibiotic rifampin was also assessed. Results: The infection was thought to have been acquired haematogenously in 16 patients and peri-operatively in 14. The median follow-up time for successfully treated cases was 39.2 months (12 to 75), whereas failure of the treatment occurred within the first year following treatment on every occasion. The infection-free survival at three years with 12 patients at risk was 59% (95% confidence interval 39% to 75%). Failure of the treatment was observed in ten of 22 PJIs (45%) treated with a two-stage revision arthroplasty, two of six (33%) treated by debridement and prosthesis retention, and in neither of the two PJIs treated with one-stage revision arthroplasty. Streptococcal PJI treated with or without rifampin included in the antibiotic regime showed no difference in treatment outcome (p = 0.175). Conclusion: The success of treatment of streptococcal PJI in our patient cohort was poor (18 of 30 cases, 59%). New therapeutic approaches for treating streptococcal PJI are needed. Cite this article: Bone Joint J 2017;99-B:653–9.